Insecticidal activity of the linear pseudoscorpion venom peptide Ammogarypin revealed by functional profiling - Pierry, Maurice; Dersch, Ludwig; Krämer, Jonas; Schulte, Lennart; Hardes, Kornelia; Kessel, Tobias; Grotmann, Jens; Seip, Maximilian; Vilcinskas, Andreas; Lüddecke, Tim (Frontiers in Pharmacology, 2025)
Some pseudoscorpions produce venom to subdue prey and their venom components may be of translational interest in agronomy and beyond. However, only very few pseudoscorpion venom peptides have been functionally characterized as of yet. Here, we carry out a bioactivity profiling of Ammogarypin, a linear venom peptide recently identified in the venom of Ammogarypus lawrencei. We show, that the peptide causes signs of spastic paralysis and fatalities when injected in Drosophila suzukii flies and low toxicity when injected in Myzus persicae aphids, while no effects were recovered when fed to both insects. The toxin further has marginal effects on growth of E. coli and S. aureus bacteria and no effect on the viability of mammalian MDCKII cells and equine erythrocytes. While our assessment revealed low potential for agricultural translation of the peptide, our data shows that Ammogarypin appears to fulfill a function in prey capture. In contrast to other linear pseudoscorpion toxins, it seems to serve only a single biological function and does not defend the venom gland against microbial colonization, nor serving as spreading factor. This study adds to the growing body of literature revolving around the biodiscovery and biochemical ecology of pseudoscorpions, some of earths smallest and least understood venomous animal lineages.